Robotic polishing of large optical components - Chen, Sulei (Cranfield University, 2014)
Lightweight space mirrors have been widely used in earth observation and astronomy applications. Many organizations and companies, such as NASA in America, ESA in Europe, SSTL in UK as well as CASC in China, have spent a lot of money and effort on researching new materials for larger size space mirrors to meet both the payload weight constraints of launch and the increased advanced manufacturing process demanded for higher observations quality. This project is aimed at robot neutral polishing of lapped, ground and polished optical substrates using an industrial FANUC robot system. The project focused on three main fields which were: robot polishing with polyurethane tool and cerium oxide, pitch polishing with pitch tool and cerium oxide, as well as polishing of a 400mm ULE component. The polishing process targets were to achieve: 1) a surface roughness (Ra) of 10 nm and a surface profile (Pt) of 6 µm and 2µm on lapped and ground substrates respectively with polyurethane based tools and 2) a surface roughness (Ra) of 2nm with a surface profile (Pt) unchanged on robot neutral polished substrates using pitch based tools. This thesis comprises four main sections: a literature review, an experimental implementation, metrology and analysis, and the final conclusions. The experiment results measured with the metrology equipment selected were analysed. Conclusions of the relationship between the polishing performance of a specific sample and the selected polishing tool, polishing slurry, tool pressure, polishing time and other parameters were drawn. Results obtained from robot neutral polishing were surface roughness (Ra) of 8-10nm and surface profile (Pt) of 6µm for 100mm square lapped and ground parts. The process scalability was demonstrated from robot neutral polishing in 45hours, a 400mm square ground component from a surface roughness (Ra) of 200nm to 10nm. There is additional work to be implemented in the future, such as the development of robot pitch polishing of robot neutral polished parts to achieve 2nm Ra.
Keywords: polyurethane polishing; ULE; fused silica; pitch; spot; groove; cerium oxide